Optically levitated nanoparticles as receiving antennas for low frequency wireless communication - Zhenhai Fu; Jinsheng Xu; Shaochong Zhu; Chaoxiong He; Xunming Zhu; Xiaowen Gao; Han Cai; Peitong He; Zhiming Chen; Yizhou Zhang; Nan Li; Xingfan Chen; et al. (PhotoniX)
Abstract Low-frequency (LF) wireless communications play a crucial role in ensuring anti-interference, long-range, and efficient communication across various environments. However, in conventional LF communication systems, their antenna size is required to be inversely proportional to the frequency, so that their mobility and flexibility are greatly limited. Here we introduce a novel prototype of LF receiving antennas based on optically levitated nanoparticles, which overcomes the size-frequency limitation to reduce the antenna size to the hundred-nanometer scale. These charged particles are extremely sensitive to external electric field as mechanical resonators, and their resonant frequencies are adjustable. The effectiveness of these antennas was experimentally demonstrated by using the frequency shift keying (2FSK) modulation scheme. The experimental results indicate a correlation between error rate and factors such as transmission rate, signal strength, and vacuum degree with a signal strength of approximately 0.1V/m and a bit error rate below 0.1%. We extend the application of levitated particle mechanical resonators as an entirely new type of compact LF antennas, which may be utilized in long-distance communications in extreme environments.